Simulium nunesdemelloi (Diptera: Simuliidae), a new species of black fly from the northwestern region of Amazonas State, Brazil - Hamada, Neusa; Pepinelli, Mateus; Hernández, Luis M. (Zootaxa, 2006)
The female, male, pupa, and larva of Simulium nunesdemelloi n. sp. are described and illustrated. The new species shares characters with species in the subgenera S. (Thyrsopelma) and S. (Trichodagmia); the pupa has 19 or 20 gill filaments, similar to the pupa of S. orbitale Lutz, which has 21 to 23 filaments. Simulium nunesdemelloi n. sp. was collected in the Alto Rio Negro region, in the northwestern part of Amazonas State, Brazil.